Clinical significance of the combined measurement of serum B7-H1 and interleukin-10 in colorectal cancer patients. Issue 18 (May 2020) - Wang, Peng; Li, Chun; Ma, Xuzhe; Gai, Xiaodong
Abstract : Abstract: Colorectal cancer (CRC) patients have been shown to express a cytokine signature that is detectable in serum and contributes to cancer pathogenesis. The objective of this study was to evaluate the potential clinical significance of preoperative circulating cytokine levels in CRC patients. The expression of serum B7-H1 and IL-10 was assessed by ELISA in 89 patients and 64 health volunteers. As a control marker, CEA serum levels were measured by electrochemical luminescence detection. The receiver operating characteristic (ROC) curve was used to analysis to demonstrate the potential diagnostic value of these biomarkers. The expression of serum B7-H1 was significantly increased in CRC patients ( P  = .001) and associated with the progression of TNM stage and a positive association with serum IL-10 levels was also evident. Furthermore, serum B7-H1 and IL-10 expression was not influenced by age, gender, tumor location, or mass, whereas a relationship existed with tumor metastasis and TNM stage. The serum levels of B7-H1 and IL-10 on the 7th postoperative day were significantly decreased compared with that of preoperative serum levels ( P  =   .001, P  =   .003 respectively). The area under the ROC curves (AUC) for B7-H1 and IL-10 were 0.7063 and 0.5706, respectively. The optimal sensitivity and specificity of B7-H1 for discriminating between colon cancer patients and healthy controls were 85.21% and 56.43%, respectively, using a cut-off value of 3.46 ng/mL. However, the combined ROC analysis using B7-H1 and IL-10 revealed an AUC of 0.8791, with a sensitivity of 90.63% and a specificity of 75.18%. The outcomes of the present study demonstrate the clinical significance of serum B7-H1 and IL-10 concentrations. Combined detection of B7-H1 plus IL-10 showed significantly increased sensitivity and specificity for discriminating between colorectal cancer patients and healthy controls compared these markers detection individual. The measurement of B7-H1 or IL-10 in sera following surgery may provide an additional tool for assessing the curative effects of surgery in CRC patients.